Adsorption isotherms in roasted specialty coffee (Coffea arabica L.): Dataset and statistical tools for optimizing storage conditions and enhancing shelf lifeMendeley Data - Gentil A. Collazos-Escobar; Andrés F. Bahamón-Monje; Nelson Gutiérrez-Guzmán (Data in Brief)
This work presents a comprehensive dataset of adsorption isotherms and infrared spectral data for roasted specialty coffee (Coffea arabica L.). The dataset includes adsorption isotherms for whole roasted beans and ground coffee at medium (850 µm) and fine (600 µm) particle sizes. Adsorption isotherms were experimentally determined using the Dynamic Dewpoint Isotherm (DDI) method, considering a water activity range from 0.1 to 0.9 and temperatures of 25, 35, and 45 °C. Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy was used to characterize the coffee samples spectrally. The dataset also provides two calibrated sorption models: Peleg and Double Logarithm Polynomial (DLP), which are highly suitable for practical applications, allowing users to predict the equilibrium moisture content of coffee as a function of water activity, temperature, and coffee type (whole beans or ground coffee). These tools offer valuable insights for researchers, coffee producers, and decision-makers in computing critical parameters related to roasted specialty coffee's shelf life, determining optimal packaging materials, and understanding the hygroscopic properties of coffee. The calibrated models could be used to optimize coffee storage processes and improve the understanding of water sorption behavior in different particle sizes. The dataset compiles the experimental adsorption isotherms and infrared spectra in Excel sheets according to the experimental conditions and replicates. Furthermore, this dataset includes different MATLAB® R2023a (The MathWorks Inc., Natick, MA, USA) files where the models have been calibrated with the experimental adsorption isotherms using the “Curve Fitting” tool and are available for their use in the coffee industry.